Benefits, Drawbacks, and the Path Forward for Nuclear Fission - Ganea, Theodore (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In nuclear fission, a radioactive material like Uranium-235 is induced to decay into a different element, converting some of its mass into energy in the process. This process extracts stupendous quantities of energy without CO2 emissions. Nuclear fission is safe, preserving lives and likely the environment, although more research is needed regarding radioactive waste; it creates a bonanza of high-paying jobs; and it is essential to replacing coal and combating climate change. High upfront costs are an issue, and nuclear fission requires significant government regulation and support; further research into thorium-based power may provide progress on cost. To save lives, I recommend significantly increasing nuclear power’s use in the United States.